Chemokines Updates - Şentürk, Murat (Biochemistry, 2023)
This book provides an overview of some of the latest developments in the medical sciences, with particular emphasis on the experimental and theoretical aspects of modern medicine. In recent years, researchers working in applied health sciences have been able to identify diseases indicated by chemokines. Among the topics discussed in this book are chemokines affecting platelet functions, cytokine levels, and oxidative stress parameters in COVID-19, chemokines at the intersection of diabetes-tuberculosis synergy, chemokines in periodontal diseases, pathogenic links between hepato-digestive disorders and periodontal conditions, and IL-inflammatory carcinogenesis. Other areas included are the role of 23 receptor gene variations, the relationship between interleukin‑5 Receptor polymorphism, and immunological parameters in children with asthma. The book's primary target audience includes students, researchers, medical practitioners, dentists, pharmacologists, and professionals interested in related fields. The book has been written by expert international scientists active in research in the health and applied sciences. We hope it will increase scientists' knowledge of the complexity of some medical approaches, and encourage both professionals and students to devote part of their future research to understanding the mechanisms and applications of chemokines.